IMPLEMENTATION OF PROJECT-BASED LEARNING IN THE FOOD CHEMISTRY COURSE THROUGH THE SOCIALIZATION OF FOOD INNOVATION AND TECHNOLOGY BY MAKING TEMPEH HEALTH SMOOTHIES - Aida Mustafida A; Celyta Nirmala Putri Talia; Nur Khofifah; Ersa Sania Azzahro'; Mirwa Adiprahara Anggarani (Universitas Negeri Surabaya, 2026)
Abstract This study aims to assess the capability of project-based learning (PjBL) methods in introducing innovations in the field of food and technology by making healthy tempeh smoothies, as a product of food chemistry courses, in order to deepen students' understanding of local foods. This study is based on the importance of understanding food chemistry that includes aspects of formulating, processing, and storing quality food products. The PjBL model was chosen because it can increase students’ learning motivation, creativity, and critical thinking skills in dealing with contextual problems. The study was conducted on 14 grade X students of Khadijah High School with a One Group Pretest-Posttest design. The research instrument was a multiple-choice test based on Bloom’s taxonomy and a Likert scale response questionnaire. The results showed a significant increase from a pretest score of 92,86 to a posttest score of 99,29. The N-Gain value of 0,89 and an effectiveness level of 88,89% indicated an increase in understanding in the high category and effective learning. Students were able to recognize tempeh as a local food with high nutritional value, understand the fermentation process, health benefits, and its potential for development into a modern beverage product. The questionnaire results showed a very positive response. The hands-on activity of making tempeh health smoothies increased student engagement, confidence, and motivation, including interest in simple entrepreneurial opportunities. Overall, PjBL learning was effective in strengthening local food literacy and fostering an appreciative and innovative attitude toward the use of tempeh as a health smoothies.